(untitled) (American Journal of Islam and Society, 2012)
This book deals with the old-new issue pertaining to the dialectics of Western, particularly the British“Islamists” collusion during the decades of the twentieth century and into the twenty-first century. The issue is old because much of such collaboration has been either known or suspected, especially during the era of the visible rise of threatening communist ideology since the Russian Revolution of 1917, as well as other socialist ideas. It is new because of the twists it has taken in the context of the sudden disappearance of the common Soviet ideological enemy, which had glued both parties to each other—and the ensuing so-called war on global terrorism. The issue is also dialectical as it pertains to the seeming love-hate relationship that permeated Western-Islamist interaction, and which despite all soundings of mutual vituperations and appearances of alleged resentment, never really stood in the way of both finding reasons and ways for colluding ...